Single Mothers and the Earned Income Tax Credit: Insurance Without Disincentives? - Kartik B. Athreya; Devin Reilly; Nicole B. Simpson (Institute for the Study of Labor (IZA), 2014)
The Earned Income Tax Credit (EITC) is the single most important transfer program in place in the United States. An aspect of the EITC that has received little attention thus far is its role as a public insurance program. Yet, the structure of the EITC necessarily protects its primary class of recipients, unskilled single mothers, against major risks they face to both wages and changes in family structure. Our study provides the first quantitative statement about the insurance provided by the EITC. We study a dynamic model of consumption, savings, and labor supply in which households face wage and demographic risk, but have only limited self-insurance capacity. We use the model to compare outcomes under the EITC to the counterfactual in which it is completely eliminated. We find that the EITC provides substantial insurance to unskilled single mothers: The program reduces consumption volatility, as measured by the coefficient of the variation, by 12 percentage points or more, even as it allows these households to save less. Importantly, this insurance provision may not be compromising incentives to work: The model suggests that the EITC increases the labor supply of unskilled single mothers substantially at the extensive margin.
Keywords: H22; J22; H24; 330; taxation and subsidies; labor supply; insurance